Heteroaryl derivatives of suvorexant as OX1R selective PET ligand candidates: Cu-mediated 18F-fluorination of boroxines, in vitro and initial in vivo evaluation - Bolik, Kim-Viktoria; Hellmann, Jan; Maschauer, Simone; Neu, Eduard; Einsiedel, Jürgen; Riss, Patrick; Vogg, Nora; König, Jörg; Fromm, Martin; Hübner, Harald; Gmeiner, Peter; Prante, Olaf (EJNMMI Research, 2024)
Background: The orexin receptor (OXR) plays a role in drug addiction and is aberrantly expressed in colorectal tumors. Subtype-selective OXR PET ligands suitable for in vivo use have not yet been reported. This work reports the development of 18F-labeled OXR PET ligand candidates derived from the OXR antagonist suvorexant and the OX1R-selective antagonist JH112. Results: Computational analysis predicted that fluorine substitution (1e) and introduction of the fluorobenzothiazole scaffold (1f) would be suitable for maintaining high OX1R affinity. After multi-step synthesis of 1a–1f, in vitro OXR binding studies confirmed the molecular dynamics calculations and revealed single-digit nanomolar OX1R affinities for 1a–f, ranging from 0.69 to 2.5 nM. The benzothiazole 1f showed high OX1R affinity (Ki = 0.69 nM), along with 77-fold subtype selectivity over OX2R. Cu-mediated 18F-fluorination of boroxine precursors allowed for a shortened reaction time of 5 min to provide the non-selective OXR ligand [18F]1c and its selective OX1R congener [18F]1f in activity yields of 14% and 22%, respectively, within a total synthesis time of 52–76 min. [18F]1c and [18F]1f were stable in plasma and serum in vitro, with logD7.4 of 2.28 ([18F]1c) and 2.37 ([18F]1f), and high plasma protein binding of 66% and 77%, respectively. Dynamic PET imaging in rats showed similar brain uptake of [18F]1c (0.17%ID/g) and [18F]1f (0.15%ID/g). However, preinjection of suvorexant did not significantly block [18F]1c or [18F]1f uptake in the rat brain. Pretreatment with cyclosporine A to study the role of P-glycoprotein (P-gp) in limiting brain accumulation moderately increased brain uptake of [18F]1c and [18F]1f. Accordingly, in vitro experiments demonstrated that the P-gp inhibitor zosuquidar only moderately inhibited polarized, basal to apical transport of 1c (p < 0.05) and had no effect on the transport of 1f, indicating that P-gp does not play a relevant role in brain accumulation of [18F]1c and [18F]1f in vivo. Conclusions: The in vitro and in vivo results of [18F]1c and [18F]1f provide a solid basis for further development of suitable OXR PET ligands for brain imaging.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Cu-mediated; F-18; Orexin receptor; PET; Suvorexant

Homobivalent Dopamine D2Receptor Ligands Modulate the Dynamic Equilibrium of D2Monomers and Homo-and Heterodimers - Ullmann, Tamara; Gienger, Marie; Budzinski, Julian; Hellmann, Jan; Hübner, Harald; Gmeiner, Peter; Weikert, Dorothée (ACS Chemical Biology, 2021)
Dopamine D2 receptors (D2Rs) are major targets in the treatment of psychiatric and neurodegenerative diseases. As with many other G protein-coupled receptors (GPCRs), D2Rs interact within the cellular membrane, leading to a transient receptor homo-or heterodimerization. These interactions are known to alter ligand binding, signaling, and receptor trafficking. Bivalent ligands are ideally suited to target GPCR dimers and are composed of two pharmacophores connected by a spacer element. If properly designed, bivalent ligands are able to engange the two orthosteric binding sites of a GPCR dimer simultaneously. Taking advantage of previously developed ligands for heterodimers of D2R and the neurotensin receptor 1 (NTSR1), we synthesized homobivalent ligands targeting D2R. Employing bioluminescence resonance energy transfer, we found that the bivalent ligands 3b and 4b comprising a 92-atom spacer are able to foster D2R-homodimerization while simultaneously reducing interactions of D2R with NTSR1. Both receptors are coexpressed in the central nervous system and involved in important physiological processes. The newly developed bivalent ligands are excellent tools to further understand the pharmacological consequences of D2R homo-and heterodimerization. Not limited to the dopaminergic system, modifying class A GPCRs' dynamic equilibrium between monomers, homomers, and heteromers with bivalent ligands may represent a novel pharmacological concept paving the way toward innovative drugs.
CRIS-Team Scopus Importer:2021-02-05

Presynaptic vesicular accumulation is required for antipsychotic efficacy in psychotic-like rats - Uzuneser, Taygun; Weiss, Eva Maria; Dahlmanns, Jana; Kalinichenko, Liubov; Amato, Davide; Kornhuber, Johannes; Alzheimer, Christian; Hellmann, Jan; Kaindl, Jonas; Hübner, Harald; Löber, Stefan; Gmeiner, Peter; et al. (Journal of Psychopharmacology, 2021)
Background: The therapeutic effects of antipsychotic drugs (APDs) are mainly attributed to their postsynaptic inhibitory functions on the dopamine D2 receptor, which, however, cannot explain the delayed onset of full therapeutic efficacy. It was previously shown that APDs accumulate in presynaptic vesicles during chronic treatment and are released like neurotransmitters in an activity-dependent manner triggering an auto-inhibitory feedback mechanism. Although closely mirroring therapeutic action onset, the functional consequence of the APD accumulation process remained unclear. Aims: Here we tested whether the accumulation of the APD haloperidol (HAL) is required for full therapeutic action in psychotic-like rats. Methods: We designed a HAL analog compound (HAL-F), which lacks the accumulation property of HAL, but retains its postsynaptic inhibitory action on dopamine D2 receptors. Results/outcomes: By perfusing LysoTracker fluorophore-stained cultured hippocampal neurons, we confirmed the accumulation of HAL and the non-accumulation of HAL-F. In an amphetamine hypersensitization psychosis-like model in rats, we found that subchronic intracerebroventricularly delivered HAL (0.1 mg/kg/day), but not HAL-F (0.3–1.5 mg/kg/day), attenuates psychotic-like behavior in rats. Conclusions/interpretation: These findings suggest the presynaptic accumulation of HAL may serve as an essential prerequisite for its full antipsychotic action and may explain the time course of APD action. Targeting accumulation properties of APDs may, thus, become a new strategy to improve APD action.
CRIS-Team Scopus Importer:2020-12-11
Keywords: behavior; Haloperidol; presynaptic accumulation; schizophrenia

Structure-based development of a subtype-selective orexin 1 receptor antagonist - Hellmann, Jan; Drabek, Matthaeus; Yin, Jie; Gunera, Jakub; Pröll, Theresa; Kraus, Frank; Langmead, Christopher J.; Hübner, Harald; Weikert, G. Dorothee; Kolb, Peter; Rosenbaum, Daniel M.; Gmeiner, Peter (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Orexins are neuropeptides that activate the rhodopsin-like G protein -coupled receptors OX1R and OX2R. The orexin system plays an im-portant role in the regulation of the sleep-wake cycle and the regu-lation of feeding and emotions. The nonselective orexin receptor antagonist suvorexant has been the first drug on the market target-ing the orexin system and is prescribed for the treatment of insomnia. Subtype-selective OX1R antagonists are valuable tools to further in-vestigate the functions and physiological role of the OX1R in vivo and promising lead compounds for the treatment of drug addiction, anx-iety, pain or obesity. Starting from the OX1R and OX2R crystal struc-tures bound to suvorexant, we exploited a single amino acid difference in the orthosteric binding site by using molecular docking and structure-based drug design to optimize ligand interactions with the OX1R while introducing repulsive interactions with the OX2R. A newly established enantiospecific synthesis provided li-gands showing up to 75-fold selectivity for the OX1R over the OX2R subtype. The structure of a new OX1R antagonist with sub-nanomolar affinity (JH112) was determined by crystallography in complex with the OX1R and corresponded closely to the docking -predicted geometry. JH112 exhibits high selectivity over a panel of different GPCRs, is able to cross the blood-brain barrier and acts as slowly diffusing and insurmountable antagonist for Gq protein acti-vation and in particular beta-arrestin-2 recruitment at OX1R. This study demonstrates the potential of structure-based drug design to de-velop more subtype-selective GPCR ligands with potentially reduced side effects and provides an attractive probe molecule and lead compound.
CRIS-Team WoS Importer:2020-08-21